Effect of Different Feeding on Uric Acid Levels in Mice (Mus musculus L.) - Helendra; Diana, Okta; atifah, Yusni (Jurnal Serambi Biologi, 2023)
Aim Uric acid is an acid that is formed from purine metabolism in the body. If uric acid levels in the blood exceed normal limits it is called hyperuricemia. Diet plays an important role in increasing or decreasing uric acid levels. Consuming foods high in purines can also increase uric acid levels. The purpose of this study was to determine the effect of different feeds on uric acid levels in mice. Methods This research is an experimental research. The research method used was a completely randomized design (CRD) with 3 treatments and 7 replications for each group. Results There is a difference in the average uric acid levels of mice in the K, P1, and P2 treatment groups. In the K treatment group, the average uric acid level of mice was 3,2 mg/dl. In the P1 treatment group, the average uric acid level of mice was 7,3 mg/dl. In the P2 treatment group, the average uric acid level of mice was 4,2 mg/dl. Main conclusions Differences in mice uric acid levels are influenced by diet, and consumption of foods high in purines. The highest average uric acid levels in mice were in the P1 treatment group of 7,3 mg/dl.